Elaborating the molecular characteristics of corals’ different tolerance to environmental stress in Sanya Luhuitou based on multi-omics analysis - Tang, Xiaoyu; Guo, Xiangrui; Wang, Hanzhang; Yang, Qingsong; Zhang, Ying; Ling, Juan; Sun, Hao; Dong, Junde; Zhang, Yanying (Frontiers in Microbiology, 2026)
IntroductionThe resistance to environmental perturbations varies significantly among coral species. Corals are holobionts that are symbiotic with dinoflagellates and microbiomes, which makes their physiological responses to environmental stress complex. In order to restore coral reefs, it is essential to discover the molecular characteristics associated with coral environmental stress tolerance and to understand the molecular mechanisms that contribute to physiological adaptation.MethodsUsing high throughput 16S rRNA gene sequencing, combined with transcriptome, proteome, and metabolome analyses, we analyzed the differences in coral associated bacterial communities between the branching coral (Pocillopora damicornis) and massive corals (Porites lutea and Galaxea fascicularis), as well as the profiling of environmental stress resistance related genes, proteins and metabolites in these coral species.ResultsThe results showed that beneficial bacteria were more abundant in massive corals than in branching corals, while pathogenic bacteria were more abundant in branching corals. Genes and proteins that can counteract environmental stress were found more abundant in branching corals as compared to massive corals. Branching corals contained higher levels of metabolites associated with environmental stress, such as LysoPC (15:0). Massive corals possess simultaneously higher basal expression genes (or proteins) involved in amino acid metabolism, which may contribute to their higher tolerance.DiscussionBased on molecular characteristics, branching corals’ resistance to environmental stress was weaker than that of massive corals, which provided a valuable reference for coral reef protection in the future.